Study on Comparative Performance of Cowpea in Rice Fallows Areas as Influence by Dates of Sowing in Ri Bhoi District of Meghalaya - Singh, M. B.; Singh, A. K.; P., Lala I.; Devi, M. B. (Indian Journal of Hill Farming, 2018)
Pulses are the second important group of crops after cereals, providing high dietary protein (20 to 25%), along with rich supplement of calcium and iron. They play an important role to enhance soil fertility through biological nitrogen fixation and also pass on the benefits to associated non legume and subsequent crops. In NER of India, farmers mostly go for monocropping of rainfed rice. It is estimated that more than 5 lakh ha of low lying area in the region remain fallows after harvest of rice during rabi season. Such fallow land can be brought under cultivation, with short duration varieties of summer pulses such as cowpea. To identify suitable date of sowing of summer pulse (cowpea) for lowland rice fallow, the current study was undertaken. The present experiment revealed that cowpea should a choice of summer pulse for cultivation in lowland rice fallows because of its consistent performance inÂ all sowing dates. It is also revealed the maximum grain yield was obtained when the crop is sown on 4th March.